Stigma and Prejudice Touchstones in Understanding Diversity in Healthcare - Parekh, Ranna; Childs, Ed W. (Current Clinical Psychiatry, 2016)
In this innovative title, the authors describe unique patient populations affected by stigma and prejudice and the prevalence of these issues to all healthcare providers. Each chapter covers the forms of prejudice and stigma associated with minority statuses, including religious minorities, the homeless, as well as those stigmatized by medical serious medical conditions, such HIV/AIDS, obesity, and substance misuse disorders. The chapters focus on the importance of recognizing biological differences and similarities within such groups and describes the challenges and best practices for optimum healthcare outcomes. The text describes innovative ways to connect in a clinical setting with people of diverse backgrounds. The text also covers future directions and areas of research and innovative clinical work being done. Written by experts in the field, Stigma and Prejudice is an excellent resource for psychiatrist, psychologists, general physicians, social workers, and all other medical professionals working with stigmatized populations.